Farmers’ intention to adopt improved technologies for disease prevention in shrimp farming in Peninsular Malaysia - Azali @ Sazali, Amira Hanani (2023)
Two marine shrimp species namely, native giant tiger prawn (Penaeus monodon) and non-native white shrimp (Penaeus vannamei) are mostly farmed in Malaysia. Diseases are undeniably the most important encounters confronted by the shrimp industry caused by bacterial, viral, fungus, and protozoa, significantly affecting the giant tiger prawn and white shrimp production. Shrimp farming should have a greater need for antibiotics and antimicrobial treatments to treat the diseases as well as to increase its production and productivity. Nevertheless, overuse of antibiotics and antimicrobial drugs had caused antimicrobial resistance (AMR) problems in shrimp farming which can cause an effect on human health and the environment in the long term. Hence, improved technologies for solving the AMR problems by eliminating the heavy usage of antibiotics in shrimp farming are needed. The main objective of this study was to determine shrimp farmers’ intention to adopt improved technologies for disease prevention in shrimp farming in Peninsular Malaysia. Using the stratified random sampling method, a total of 123 shrimp farmers located in Peninsular Malaysia were selected based on four (4) regions, and a structured questionnaire was used to obtain responses from the shrimp farmers. Several statistical analyses were carried out to analyse the data such as descriptive analysis, Pearson correlation analysis, Chi-square analysis, factor analysis, and logistics regression analysis. The results showed that most of the shrimp farmers have adequate knowledge (63.4%, n=78) of the improved technologies – probiotic, antibody, and green water systems, whereas the remaining 36.6% (n=45) of the shrimp farmers have inadequate knowledge. Most shrimp farmers have a favourable attitude (78.0%, n=96) towards adopting the improved technologies in their farm, while 22.0% (n=27) have an unfavourable attitude. Most of the shrimp farmers (74.0%, n= 91) have a high intention to adopt improved technologies while 26.0% (n=32) of shrimp farmers have a low intention. There was a moderately significant positive relationship between the shrimp farmers’ knowledge and their attitude to adopt improved technologies for disease prevention in shrimp farming. Educational level, farmers’ experience, farm size, training, and monthly revenue were significantly associated with shrimp farmers’ intention to adopt the improved technologies. Four (4) factors were extracted from factor analysis namely attitude, perceived behavioural control, subjective norm, and perceived resources and these factors were further measured in logistic regression analysis. Farmers’ educational level, farmers’ experience, attitude, subjective norm, and perceived resources were identified as the factors that influenced shrimp farmers’ intention to adopt improved technologies. Further, farmers’ attitude was revealed as the most influential factor that influenced shrimp farmers’ intention to adopt improved technologies for disease prevention in their farming. The study indicated that the majority of shrimp farmers had a high intention to adopt improved technologies. Attending relevant training programs can increase the farmers’ knowledge and having a good and strong collaboration with a few shrimp farms can promote the benefits of improved technologies on a broad scale. Government should provide relevant training programs, webinars, hands-on workshops, and financial incentives to motivate the farmers in spreading their knowledge of the importance of adopting these technologies.